NEED ANALYSIS OF ENGLISH FOR SPECIFIC ACADEMIC PURPOSES OF FIRST YEAR ECONOMICS STUDENTS AT EKASAKTI UNIVERSITY - Franchisca, Sherly (RC-INSTITUT, 2018)
English for Economics in higher education is related to English for Specific Academic Purposes. English for Economics is a skill based course designed specifically for students economics who are about to enter English subject. It provides carefully graded practice and progressions in the key academic skills that all students need, such as listening to lectures and speaking in seminars. It also equips students with the special language they need to participate carefully within an economics department. There is also a focus throughout on the key economics vocabulary that students will need. Keywords: Need Analysis, English for specific academic purposes, first year aconomic students at Ekasakti University